MFF-dependent mitochondrial fission regulates presynaptic release and axon branching by limiting axonal mitochondria size. Issue 1 (December 2018) - Lewis, Tommy; Kwon, Seok-Kyu; Lee, Annie; Shaw, Reuben; Polleux, Franck
Abstract Neurons display extreme degrees of polarization, including compartment-specific organelle morphology. In cortical, long-range projecting, pyramidal neurons (PNs), dendritic mitochondria are long and tubular whereas axonal mitochondria display uniformly short length. Here we explored the functional significance of maintaining small mitochondria for axonal development in vitro and in vivo. We report that the Drp1 'receptor' Mitochondrial fission factor (MFF) is required for determining the size of mitochondria entering the axon and then for maintenance of their size along the distal portions of the axon without affecting their trafficking properties, presynaptic capture, membrane potential or ability to generate ATP. Strikingly, this increase in presynaptic mitochondrial size upon MFF downregulation augments their capacity for Ca2+ ([Ca2+ ]m ) uptake during neurotransmission, leading to reduced presynaptic [Ca2+ ]c accumulation, decreased presynaptic release and terminal axon branching. Our results uncover a novel mechanism controlling neurotransmitter release and axon branching through fission-dependent regulation of presynaptic mitochondrial size. It is unclear how and why axonal mitochondria are kept so small in axons. Authors show here that MFF-mediated fission is required for determining the size of mitochondria both entering and along the axon, and this is critical for mitochondrial calcium uptake capacity, neurotransmitter release properties and axon branching.